The Effect Of Brand Image, Quality And Price Of Immunomodulator Products On Satisfaction And Its Impact On Consumer Loyalty In Jabodetabek: PENGARUH CITRA MEREK, KUALITAS DAN HARGA PRODUK IMUNOMODULATOR TERHADAP KEPUASAN DAN DAMPAKNYA PADA LOYALITAS KONSUMEN JABODETABEK - Fauzi Setyo Fandheo; Shirly Kumala; Lies Putriana (Jurnal Riset Bisnis, 2025)
When the immune system is not working properly, the body is susceptible to disease. There are some ways to boost the immune system; consuming herbs or supplements which functioned immunomodulators. Before buying a product, potential consumers usually considerate the brand, quality, and price of the product that will be purchased. Stimuno and Imboost are the top brands category of immune system vitamins on the Top Brand Index (TBI) from 2015 until 2021. This study to analyze the effect of brand image, quality, and price of immunomodulator products from the stimuno and imboost brands on satisfaction and their impact on customer loyalty. This research is explanatory research – quantitative data - probability sampling method - purposive sampling technique. The obtained data then tested for the validity, reliability, and suitability of each variable using SEM PLS (Structural Equation Model Partial Least Square) software. The results of the analysis show that brand image (3.797 and 0.000), quality (2.037 and 0.042), and product price (11.491 and 0.000) have a t-value > 1.96 and p-value <0.05 directly on customer satisfaction. Brand image (3.198 and 0.001), quality (1.967 and 0.049), and product price (3.912 and 0.000) indirectly through customer satisfaction have t- value > 1.96 and p-value < 0.05. Based on the results of the analysis, it can be concluded that brand image, product quality, and price directly have a positive and significant effect on customer satisfaction. Brand image, product quality, and price indirectly through customer satisfaction have a positive and significant effect on customer loyalty.